Recurrent spontaneous gastric perforations in a neonate with renal tubular dysgenesis: A case report - Mashael AlSiddiqi; Safaa Najar; Sami Taha; Hassan Baghazal; Noora Alshahwani (Journal of Pediatric Surgery Case Reports)
Introduction: Neonatal gastric perforation (NGP) is a very rare, life-threatening condition. Management can be complicated in patients with co-morbidities. Recurrent gastric perforation is even more rare. Case presentation: A 33 6/7 male was born by cesarean section and had a birth weight of 2300g. His mother was gravida 3/para 1, otherwise healthy. The parents were third-degree cousins. Prenatal ultrasounds showed severe oligohydramnios with bilateral hyperechogenic kidneys. On physical exam, he had subtle facial dysmorphism, rocker bottom feet, stiff joints, and long slender fingers. He developed respiratory distress shortly after birth, which required intubation and mechanical ventilation. He was made nil per os (NPO), and antibiotics were started. At 20 hours of life, he had a sudden deterioration with desaturations, hypotension, and severe abdominal distension. Abdominal X-ray showed free air in the peritoneal cavity. We placed a peritoneal drain. One day later he reaccumulated air. We suspected that he could have renal tubular dysgenesis (RTD) given that he had no urine output. One day later he was taken to the operating room for an exploratory laparotomy. We found a large perforation in the lesser curve of the stomach. We repaired the perforation and placed a peritoneal dialysis catheter. Four days later he was re-explored for pneumoperitoneum. We found a perforation in the anterior wall of the stomach and repaired it in 2 layers. There was no bowel obstruction distal to the stomach. Three days later, we re-explored him for pneumoperitoneum and found a perforation on the posterior wall. The two other repairs were intact. We closed the perforation and placed a gastrostomy. Thirteen days later he was re-explored for pneumoperitoneum, and we found a second perforation in the posterior wall. Feedings were slowly started. His renal function improved, and he was discharged home at 3 months of age. Conclusion: The association of RTD and spontaneous gastric perforation has not been previously reported. We do not know if there is a causality between the two conditions but based on our case, we recommend that patients with RTD should be closely watched for signs of gastric perforation.